Analysis of Project Cost Estimation as an Effort to Improve Construction Project Time Performance - Semedi Napitupulu; Mardiaman; Syafiatun Siregar (Universitas Negeri Padang, 2025)
Construction project management aims to manage time, cost, and resources effectively and efficiently so that the project can be completed according to plan. However, in practice, many construction projects, especially in the Medan City area, experience significant delays and cost overruns. This is due to inaccurate cost and time estimates, as well as lack of attention to various internal factors. This study aims to analyze project cost estimation as an effort to improve construction project time performance. Data were collected from 201 respondents working in the construction sector with varying educational backgrounds and work experiences. The analysis was conducted using the covariance-based Structural Equation Modeling (CB-SEM) approach with the help of AMOS software, as well as the Maximum Likelihood Estimation technique to estimate project duration. The results of the study indicate that project cost estimation is significantly influenced by three main factors, namely Budgeted Cost of Work Schedule (BCWS), Actual Cost of Work Performed (ACWP), and Budgeted Cost of Work Performed (BCWP). Meanwhile, the time performance factor does not have a significant effect on cost estimation. On the other hand, project time performance is influenced by the availability of labor, main equipment, funding, and implementation methods. The feasibility test of the model using Goodness of Fit indicators such as CMIN, RMSEA, TLI, NFI, and CFI shows that the model used meets the Absolute Fit Model criteria, so it can be concluded that the relationship between variables in this research model is valid and can be used to support decision making in construction project management.